Perceptions of The Importance of Halal Certification: A Study on Religious Tourism SMES of Syaikhona Kholil Tomb, Bangkalan - Fadila Febriana Tenesha; Nasrulloh Nasrulloh (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2023)
This study aims to analyze the perceptions of MSEs at the religious tourism site of Syaikhona Kholil Bangkalan Cemetery regarding the importance of halal certification, as well as analyze the inhibiting factors in carrying out halal certification. This article uses a qualitative research method with a descriptive analysis study approach. The results showed that as many as 9 or 63% of informants had the perception that halal certification was not important, and only 6 or 37% of informants had the perception that halal certification was important. Meanwhile, the inhibiting factor experienced by MSEs at the religious tourism site of Syaikhona Kholil Bangkalan Cemetery to carry out halal certification was the lack of information obtained as many as 12 or 80% of new informants obtained information related to halal certification from researchers, and only 3 or 20% obtained information from other people. Penelitian ini bertujuan untuk menganalisis persepsi UMK di tempat wisata religi Makam Syaikhona Kholil Bangkalan terhadap pentingnya sertifikasi halal, serta menganalisis faktor penghambat dalam melakukan sertifikasi halal.Artikel ini menggunakan metode penelitian kualitatif dengan pendekatan studi yang bersifat analisis deskriptif. Hasil penelitian menunjukkan bahwa sebanyak 9 atau 63% informan berpersepsi bahwa sertifikasi halal tidak penting, dan hanya 6 atau 37% informan berpersepsi bahwa sertifikasi halal penting. Sedangkan faktor penghambat yang dialami UMK di tempat wisata religi Makam Syaikhona Kholil Bangkalan untuk melakukan sertifikasi halal yaitu minimnya informasi yang diperoleh sebanyak 12 atau 80% informan baru mendapatkan informasi terkait sertifikasi halal dari peneliti, dan hanya 3 atau 20% mendapatkan informasi dari orang lain.